Investigating the contextual influences shaping recycling behaviours - Ng, Ai Sian (Nanyang Technological University, 2022)
Though the Paris Agreement came into effect in 2016 to unite all nations to act now to achieve carbon-neutral earth by 2050, devastating climate change effects are increasing globally. Despite the renewed hope of international collaboration led by superpowers, concerted efforts are critically needed now to transform our current production and consumption modes to achieve the targeted carbon emission reductions. Personal motivators, coupled with team efforts, are needed even more so now to augment policies to nudge one toward living more sustainably to make a carbon-neutral world a reality in 2050. This thesis thus aimed to build a contextual influence model and contribute a framework to integrate theory and practice to identify contextual influences that can be used to effectively nudge one to willingly recycle as a pragmatic approach to minimise the post-consumption harm on the environment. The model was developed to identify the drivers for adults to recycle, with a secondary focus on the youth respondents who were identified as potential concerns or game changers in ensuring environmental sustainability.